2020
DOI: 10.1039/c9ra10513a
|View full text |Cite
|
Sign up to set email alerts
|

Efficient donor–acceptor emitter based nonsymmetrical connection for organic emitting diodes with improving exciton utilization

Abstract: New strategy is developed to construct efficient blue emissive materials using unsymmetrical connection with identical phenanthrimidazole groups leads to donor–acceptor (D–A) architecture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 79 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…In continuation of our research using the HLCT-emissive state strategy, 10 we report M-shaped blue emissive materials with the HLCT emissive state, namely 4′-(( E )-2-(1-(4-(diphenylamino)phenyl)-1 H -phenanthro[9,10- d ]imidazol-2-yl)vinyl)- N -(4′-(( E )-2-(1-(4-(diphenylamino)phenyl)-1 H -phenanthro[9,10- d ]imidazol-2-yl)vinyl)-[1,1′-biphenyl]-4-yl)- N -phenyl-[1,1′-biphenyl]-4-amine (TPA–2SPPITPA). The non-doped BOLEDs based on TPA–2SPPITPA/TPA–2PPITPA show a maximum EQE of 6.13/5.82% with small efficiency roll-off (1.63/3.0%), CE of 5.92/5.43 cd A −1 , power efficiency (PE) of 5.15/4.98 lm W −1 and CIE of (0.15, 0.07)/(0.15, 0.07).…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…In continuation of our research using the HLCT-emissive state strategy, 10 we report M-shaped blue emissive materials with the HLCT emissive state, namely 4′-(( E )-2-(1-(4-(diphenylamino)phenyl)-1 H -phenanthro[9,10- d ]imidazol-2-yl)vinyl)- N -(4′-(( E )-2-(1-(4-(diphenylamino)phenyl)-1 H -phenanthro[9,10- d ]imidazol-2-yl)vinyl)-[1,1′-biphenyl]-4-yl)- N -phenyl-[1,1′-biphenyl]-4-amine (TPA–2SPPITPA). The non-doped BOLEDs based on TPA–2SPPITPA/TPA–2PPITPA show a maximum EQE of 6.13/5.82% with small efficiency roll-off (1.63/3.0%), CE of 5.92/5.43 cd A −1 , power efficiency (PE) of 5.15/4.98 lm W −1 and CIE of (0.15, 0.07)/(0.15, 0.07).…”
Section: Introductionmentioning
confidence: 84%
“…Third-generation organic emitters, namely thermally activated delayed fluorescence (TADF) 8 and hybridized local and charge-transfer (HLCT) 9,10 excited-state emitters, which render 100% exciton utilization efficiency (EUE) while avoiding noble metals, have been considered as potential candidates. The long exciton lifetime of TADF emitters (D–A molecules with small splitting energy) tends to cause serious efficiency roll-off under high current due to triplet–triplet annihilation (TTA), whereas short exciton lifetimes of HLCT emitters are beneficial to suppress exciton annihilation and thus improve efficiency roll-off.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S3 & S4). The large ΔE T1 -T2 between T 1 and T 2 states of NSPI-DVP (1.19 eV) and CNSPI-DVP (1.60 eV) assisted the fast RISC by the restriction of internal conversion, called hot-exciton mechanism and ΔE T1-T2 of CNSPI-DVP is larger than NSPI-DVP due to cyano group (Figure 4 & Figure S3) [20][21][22][23] [k r s/f (10 8 s -1 ) -1.21/2.41: k nr s/f (10 8 s -1 ) -1.07/2.37 and CNSPI-DVP (k r s/f (10 8 s -1 ) -1.90/2.51: k nr s/f (10 8 s -1 ) -1.65/2.45]. The increase of k r and decrease of k nr of CNSPI-DVP and NSPI-DVP is in line with the aim of our design strategy.…”
Section: Photophysical Propertiesmentioning
confidence: 99%
“…Phenanthroimidazoles with C2 substitution developed effective conjugation and results in deep blue emission, whereas N1 substitution does not affect the optical properties significantly because of perpendicular configuration [15][16][17][18][19]. Though C2 and N1 substituted 3 phenanthroimidazoles have been studied widely, C6 and C9 substituted phenanthrimidazole derivatives have not been analysed broadly [20,21]. Recently, our research group reported C6 /C9 as well as C5/C10 substituted phenanthrimidazole derivatives (D-A) with excellent efficiency and low roll-off efficiency [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%